Core Domain Set Selection According to OMERACT Filter 2.1: The OMERACT Methodology - Maxwell, Lara J; Beaton, Dorcas E; Shea, Beverley J; Wells, George A; Boers, Maarten; Grosskleg, Shawna; Bingham, 3rd, Clifton O; Conaghan, Philip G; D'Agostino, Maria Antonietta; de Wit, Maarten; Gossec, Laure; March, Lyn; et al. (Journal of rheumatology, 2019)
To describe the Outcome Measures in Rheumatology (OMERACT) Filter 2.1 methodology for core domain set selection. The "OMERACT Way for Core Domain Set selection" framework consists of 3 stages: first, generating candidate domains through literature reviews and qualitative work, then a process of consensus to obtain agreement from those involved, and finally formal voting on the OMERACT Onion. The OMERACT Onion describes the placement of domains in layers/circles: mandatory in all trials/mandatory in specific circumstances (inner circle); important but optional (middle circle); or research agenda (outer circle). Five OMERACT working groups presented their core domain sets for endorsement by the OMERACT community. Tools including a workbook and whiteboard video were created to assist the process. The methods workshop at OMERACT 2018 introduced participants to this framework. The 5 OMERACT working groups achieved consensus on their proposed core domain sets. After the Methodology Workshop training exercise at OMERACT 2018, over 90% of participants voted that they were confident that they understood the process of core domain set selection. The methods described in this paper were successfully used by the 5 working groups voting on domains at the OMERACT 2018 meeting, demonstrating the feasibility of the process. In addition, participants at OMERACT 2018 expressed increased confidence and understanding of the core domain set selection process after the training exercise. This methodology will continue to evolve, and we will use innovative technology such as whiteboard videos as a key part of our dissemination and implementation strategy for new methods.